Candida Albicans Candidalysin ECE1 Gene − A Potent Virulence Factor for Oral Squamous Cell Carcinoma and Oral Potentially Malignant Disorders - Mani B. Subramani; Krishnan Mahalakshmi; Bharathy Jaya; Sankar Leena Sankari; Venkatesan N. Kumar (Indian Journal of Dental Research)
Background: Candidalysin has been isolated initially from a pathogenic human fungus. The extent of cell elongation 1 (ECE1) gene codes for candidalysin of Candida albicans (C. albicans). This toxin is most important for epithelial immune activation, invasiveness and infection of the oral mucosa. Aim: This study is aimed at detecting the ECE1 gene in C. albicans isolates from oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs). Methods and Material: A total of 60 C. albicans isolates from OSCC (n = 23), OPMDs (n = 23) and healthy subjects (n = 14) were subjected to a polymerase chain reaction (PCR) for the detection of ECE1 gene. A high prevalence of the ECE1 gene was observed among the C. albicans isolates from OSCC and OPMD compared to the isolates from healthy subjects. Statistical significance was observed for both OSCC and OPMD groups compared to the healthy group. Results and Conclusion: The results suggest the significant role of candidalysin in oral oncogenesis. The high odds and risk ratio specify a strong association between candidalysin and these conditions. Screening this gene in a large number of isolates would further reinforce their role in oncogenesis. Future studies in characterizing their virulence on normal cell lines would clarify the importance of candidalysin in promoting oncogenesis.